Effect of Menopause Duration and Biopsychosocial Factors on Quality of life of Women in Kediri District, East Java - Sari, Nunik Ike Yunia; Adriani, Rita Benya; Mudigdo, Ambar (Journal of Maternal and Child Health, 2017)
Background: Menopause is defined as the point in time when menstrual cycles permanently cease due to the natural depletion of ovarian oocytes from aging. Studies have shown,